AN ANALYSIS OF STUDENTS' ERRORS IN USING PERSONAL PRONOUNS IN WRITING DESCRIPTIVE TEXT IN THE TENTH GRADE OF SMA NEGERI 1 TANJUNG PURA - Amnun Isnawati Harahap (English Lecturers and Teachers Association (ELTA), 2023)
The purpose of this study were to identify the types of errors made by tenth-grade students of SMA Negeri 1 Tanjung Pura in the use of personal pronouns in writing descriptive text, as well as the reasons for these errors. A purposive sampling technique was used to select the respondents. There were 36 students of grade X of MIA 1 were taken as samples. This study employed a descriptive methodology. The researcher administered a written test requiring students to compose descriptive texts about a person to collect the data. As research participants were students in the tenth grade will be administered the examination. The purpose is to identify errors made by students. It is also necessary to know what types of errors students make. The data analysis revealed that the tenth-grade students of SMA Negeri 1 Tanjung Pura made the following quantifier errors when writing descriptive texts: omission, additional, misformation, and misordering. The majority of errors were omission errors with a value of 36.84%, followed by addition errors with a value of 84 or 20.74%, misformation errors with a percentage of 32.10%, and misordering errors with a value of 43 or 10.62%. Based on the results of the questionnaire, it was determined that the student's lack of motivation to learn was largely attributable to their difficulties with reading, writing, and comprehension, especially in terms of applying what they learn to real-world situations. Keywords: Error analysis, Personal pronouns, Descriptive Text.